2018
DOI: 10.1186/s12877-017-0693-z
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the link between cognitive decline and masticatory dysfunction

Abstract: Age-related decline in cognitive functions and dementia are major challenges in geriatric healthcare. Accumulating evidence from clinical, epidemiological and animal research suggests that tooth loss may be a risk factor for the decline of cognitive functions. This issue highlights the role of the brain-stomatognathic axis in geriatric medicine. Whether input from the stomatognathic apparatus can affect the brain remains an open debate. By revisiting the evidence published in the past five years, we argue that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 89 publications
(150 reference statements)
2
80
2
3
Order By: Relevance
“…Therefore, synthesising the loci commonly activated during teeth occlusion would be a critical step in establishing imaging markers for brain representation related to orofacial sensorimotor functions. Finally, accumulating evidence has shown that the brain and the stomatognathic system engage in bidirectional communication . A hotly debated issue is whether an association exists between declining masticatory function and declining cognitive function .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, synthesising the loci commonly activated during teeth occlusion would be a critical step in establishing imaging markers for brain representation related to orofacial sensorimotor functions. Finally, accumulating evidence has shown that the brain and the stomatognathic system engage in bidirectional communication . A hotly debated issue is whether an association exists between declining masticatory function and declining cognitive function .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, accumulating evidence has shown that the brain and the stomatognathic system engage in bidirectional communication. 15 A hotly debated issue is whether an association exists between declining masticatory function and declining cognitive function. 56,57 A potential application of fMRI is to explore the neural mechanisms underlying this potential association and to identify, for example, the relationship between chewing-related S1/M1 representations (an index of oral function) and changes in hippocampal/prefrontal activation (an index of cognitive function).…”
Section: Clinical Implications and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been growing evidence suggesting that poor oral health is associated with cognitive impairment in older adults. The issue highlights the role of the brain-stomatognathic axis in geriatric medicine [50]. Previous studies have demonstrated that suboptimal dentition (<20 teeth) and poorer mastication are associated with a higher risk of dementia or cognitive decline [20,51].…”
Section: Discussionmentioning
confidence: 99%